Outcomes of Descemet's stripping endothelial keratoplasty in eyes with failed therapeutic penetrating keratoplasty. (7th February 2013) - Chaurasia, Sunita; Murthy, Somasheila; Ramappa, Muralidhar; Mohamed, Ashik; Garg, Prashant
Abstract. Purpose: To report the results of Descemet's stripping endothelial keratoplasty (DSEK) for failed therapeutic penetrating keratoplasty (PK). Methods: Twenty‐seven eyes of 27 patients undergoing DSEK for failed therapeutic PK were analysed. Results: The mean age of the patients was 36 ± 13.9 years (range: 14–70 years). The median size of the therapeutic graft was 10 mm (inter‐quartile range; IQR 9.5–11 mm). Descemet's membrane stripping was performed in all eyes. Graft clarity was achieved in 20/27 eyes. Six eyes had primary graft failure, and one had interface keratitis in the early postoperative period. In all eyes with primary graft failure, there was progressive stromal vascularization, which led to haziness in the graft. Late postoperative complications were rejection in four eyes, infection in two eyes, secondary graft failure in one eye and vortex keratopathy in one eye. Graft size was found to be a significant risk factor for graft rejection in this series. At the last follow‐up visit, the best‐corrected visual acuity was ≥20/40 in 5/27 eyes (18.5%), 20/60–20/40 in 12/27 eyes (44.4%), 20/100–20/60 in 3/27 eyes (1.5%) and ≤20/200 in 7/27 eyes (25.9%). Conclusions: Considering the limited success of repeat PK in failed large therapeutic keratoplasty, DSEK is a viable option for visual rehabilitation in these eyes, however; visual acuity may be limited due to sub‐epithelial/stromal or interface scarring.